KERENTANAN BEBERAPA JENIS KAYU TERHADAP SERANGAN KUMBANG AMBROSIA - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1992)
Ambrosia  beetles  belong to the most destructive wood borers  that attack fresh cut logs. To determine the damage of some wood species caused by the pests, a field study was conducted by calculating the intensity  of the beetle infestation on the surface of logs in a log yard of a logging operation, and on the surface  of cores of peeled logs of a plywood mill.Observations on the yard showed that most of the logs had been severely  damaged by the beetles. Hundreds  of holes per-square meter were found on the surface of the logs. Meranti (Shorea  spp) logs might  belong to the most susceptible ones, and then consecutively  followed by the bangkirai (S.laevifolia),   mersawa (Anisoptera   spp), keruing (Dipterocarpus spp), and others. Only few logs seemed to be intact.Many holes of the beetle infestation were also appeared on the surface of cores of the meranti  species, but not so on the keruing's.  That  could be implied  that the beetles attacking the meranti  are able to tunnel  very deep, to reach the heart of the wood group.